AUDIT KOMUNIKASI DI BIRO ORGANISASI DAN REFORMASI BIROKRASI SEKRETARIAT DAERAH PROVINSI DKI JAKARTA - Tsabdany Tzarauliarany Anagusti (2021)
The Bureau of Organization and Reformation of the Regional Secretariat of DKI Jakarta Province is a bureaucratic reformation agency at the DKI Jakarta Province level that has a clear communication policy. However, the internal communication practices that are carried out have never been measured regarding the effectiveness of the communication. The purpose of this research is to describe the performance of organizational communication at the Bureau ORB by conducting a communication audit. This study uses a quantitative method with a descriptive approach. Communication audits are carried out using International Communication Association (ICA) standards which are analyzed by using Importance Performance Analysis (IPA) and categorical analysis. The analysis was carried out on the eight dimensions of the communication audit there are information received, sending information to others, follow-up on information sent, sources of information, timeliness of information, organizational communication relationships, organizational outcomes, channels of communication. The sample in this study was 45 active employees of the ORB Bureau. The results obtained are that the implementation of eight dimensions in the communication audit has been carried out effectively at The Bureau of Organization and Reformation of the Regional Secretariat of DKI Jakarta Province.